MEANS OF CREATING THE ADVERTISING EFFECTS IN THE CREOLIZED TEXTS OF MARKETING COMMUNICATION - Olga A. Selemeneva (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2019)
The article discusses the issue of linguistic and paralinguistic means of creating some psychological techniques in marketing communication. Advertising text is considered as an example of a complex linguistic-and- visual phenomenon, which is represented by two heterogeneous parts: verbal and nonverbal. The author identifies and describes the system of means aimed at forming the effects of recipient’s emotional involvement and gradually increasing attention. The study is carried out on the material of creolized commercial advertising texts published in international and Russian magazines in 2018. Verbal means of creating the effect of emotional involvement includes the words with semantic component of intellectual and aesthetic evaluation, abstract nouns, declarative exclamatory sentences and imperatives. The effect of gradually increasing the recipient’s attention is achieved by using the words of utilitarian, normative and teleological evaluation, some affixal morphemes, such as: ультра-, сверх-, супер-; adjectives in comparative and superlative degree, cardinal numerals, lexical repetitions, interrogative sentences, parceled and compressed utterances, expressive syntactic constructions and other means. On the nonverbal level, the effects of emotional experiences, and the effect of gradually increasing the recipient’s attention are achieved through paralinguistic means: type variation, the combination of colours, spatial-planar variation of the text, the images.